2016
DOI: 10.1155/2016/6570671
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Proliferation of Porcine Bone Marrow Mesenchymal Stem Cells Induced by Extracellular Calcium is Associated with the Activation of the Calcium‐Sensing Receptor and ERK Signaling Pathway

Abstract: Porcine bone marrow mesenchymal stem cells (pBMSCs) have the potential for application in regenerative medicine. This study aims to investigate the effects of extracellular calcium ([Ca2+]o) on pBMSCs proliferation and to explore the possible underlying mechanisms. The results demonstrated that 4 mM [Ca2+]o significantly promoted pBMSCs proliferation by reducing the G0/G1 phase cell percentage and by increasing the S phase cell proportion and the proliferation index of pBMSCs. Accordingly, [Ca2+]o stimulated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…The data were analyzed by MultiCycle for Windows software. Proliferation index (PI) = (S + G2/M)/(G0/G1 + S + G2/M) × 100% (Ye et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were analyzed by MultiCycle for Windows software. Proliferation index (PI) = (S + G2/M)/(G0/G1 + S + G2/M) × 100% (Ye et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 5 × 10 4 PMECs were plated in 12‐well plates and subjected to 0, 10, and 600 µM of NaHS for 4 days, with six duplicate wells per group. The mRNA expression of Cyclin A2, Cyclin B1, Cyclin D3, Cyclin E2, P21, and PCNA were examined by real‐time quantitative PCR as previously described (Ye et al, ). Primer sequences (with their respective PCR fragment lengths) are shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ionomycininduced the increase of cytosolic Ca 2+ enhances the proliferation of primary mouse bone marrow mesenchymal stem cells (BMSCs) but not differentiation [32]. And high extracellular Ca 2+ promotes the proliferation of BMSCs via a calcium-sensing receptor and ERK signalling pathway [33]. However, several papers have reported that high extracellular Ca 2+ enhances adipogenesis probably through L-type Ca v channel [34] and calcium-sensing receptor [35] in porcine BMSCs.…”
Section: Calcium Signalling In Adipogenesismentioning
confidence: 99%
“…The protein of pBMSCs and iWAT was extracted and Western blot analysis was performed as previously described [25]. We used anti-PPARγ …”
Section: Western Blot Analysismentioning
confidence: 99%